Eliciting Dose and Safety Outcomes From a Large Dataset of Standardized Multiple Food Challenges - Purington, Natasha; Chinthrajah, R. Sharon; Long, Andrew; Sindher, Sayantani; Andorf, Sandra; O'Laughlin, Katherine; Woch, Margaret A.; Scheiber, Alexandra; Assa'ad, Amal; Pongracic, Jacqueline; Spergel, Jonathan M.; Tam, Jonathan; et al. (Frontiers in Immunology, 2018)
Background. Food allergy prevalence has continued to rise over the past decade. While studies have reported threshold doses for multiple foods, large-scale multi-food allergen studies are lacking. Our goal was to identify threshold dose distributions and predictors of severe reactions during blinded oral food challenges (OFCs) in multi-food allergic patients. Methods. A retrospective chart review was performed on all Stanford-initiated clinical protocols involving standardized screening OFCs to any of 11 food allergens at 7 sites. Interval-censoring survival analysis was used to calculate eliciting dose (ED) curves for each food. Changes in severity and ED were also analyzed among participants who had repeated challenges to the same food. Results. Of 428 participants, 410 (96%) had at least one positive challenge (1445 standardized OFCs with 1054 total positive challenges). Participants undergoing peanut challenges had the highest ED50 (29.9 mg), while those challenged with egg or pistachio had the lowest (7.07 or 1.7 mg, respectively). The most common adverse event was skin related (54%), followed by gastrointestinal (GI) events (33%). A history of asthma was associated with a significantly higher risk of a severe reaction (hazard ratio [HR]: 2.37, 95% confidence interval [CI]: 1.36, 4.13). Higher values of allergen-specific IgE (sIgE) and sIgE to total IgE ratio (sIgEr) were also associated with higher risk of a severe reaction (1.49 [1.19, 1.85] and 1.84 [1.30, 2.59], respectively). Participants undergoing cashew, peanut, pecan, sesame, and walnut challenges had more severe reactions as ED increased. In participants who underwent repeat challenges, the ED did not change (p=0.66), but reactions were more severe (p=0.02). Conclusions. Participants with a history of asthma, high sIgEr, and/or high values of sIgE were also found to be at higher risk for severe reactions during food challenges. These findings may help to optimize food challenge dosing schemes in multi-food allergic, atopic patients, specifically at lower doses where the majority of reactions occur. Trials Registration Number: ClinicalTrials.gov number NCT03539692; https://clinicaltrials.gov/ct2/show/NCT03539692